Odpowiedzi

2010-03-12T16:45:32+01:00
H=a-1
h=(a*pierw.3)/2
a-1=(a*pierw.3)/2 /*2
2a-2=a*pierw.3
2a - a*pierw.3 = 2
a(2-pierw.3) = 2 /:(2-pierw.3)
a = 2 / (2-pierw.3)
a = 2*(2+pierw.3) / (2-pierw.3) * (2+pierw.3)
a = 4 + 2*pierw.3 / 4-3
a = 4 + 2*pierw.3
9 3 9
2010-03-12T16:46:41+01:00
A-1=a√3/2
2a-2=a√3
2a-a√3=2
a(2-√3)=2
a= 2/2-√3=2(2+√3)/(2-√3)(2+√3)=4+2√3/4-3 = 4+2√3
9 3 9
Najlepsza Odpowiedź!
2010-03-12T16:46:48+01:00
A=bok
h=wysokość
h=a-1

a√3:2=a-1
a√3=2(a-1)
a√3=2a-2
a(√3-2)=-2
a=-2:(√3-2
a=2√3+4= bok trójkąta
17 3 17